PERSEPSI PENGUNJUNG TERHADAP WISATA ALAM AIR TERJUN ANGLO DI KABUPATEN PESAWARAN - Permana, Galih W; Herwanti, Susni; Setiawan, Agus; Yuwono, Slamet B; Febryano, Indra G (MAKILA, 2023)
Visitor perception is essential in the development of tourist destinations. This study aimed to measure visitors' perceptions of Anglo Waterfall nature tourism in Pesawaran Regency, Lampung Province. Data collection was carried out through observation and interviews using a questionnaire. Visitor perception data were analyzed descriptively and quantitatively using a Likert Scale. The study results show that visitors' perceptions of aspects of tourist attraction are in the reasonably good category with unspoiled environmental conditions. Visitors' perceptions of the promotion and information aspects are classified as not good because promotional activities on social media still need to be improved. Aspects of facilities, in general, are categorized as quite good with some additions and physical maintenance; the quality of the waterfall is classified as quite good, but the cleanliness of the tourist sites needs attention. Managers must add promotional activities and tourist information, add and maintain physical facilities visitors require, and conduct evaluations for optimal tourism development.